Ethanol consumption increases rat stress hormones and adrenomedullary gene expression - Patterson-Buckendahl, Patricia; Kubovcakova, Lucia; Krizanova, Olga; Pohorecky, Larissa A.; Kvetnansky, Richard (Alcohol (Fayetteville, N.Y.), 2005)
Numerous reports document altered drinking behavior following acute stressors but few describe physiological responses to acute stress of chronic ethanol consuming subjects. We tested rats' responses to 120-min foot restraint immobilization (Immo) after 1 week of liquid diet containing 5% wt/vol ethanol (ethanol-fed). Controls consumed isocaloric liquid diet ad libitum (adlib-fed) or in amounts equal to that of ethanol-fed subjects on the previous day (pair-fed). Each rat was implanted with a tail artery cannula on day 7 to allow remote blood collection before and during Immo on day 8. Plasma epinephrine (Epi); norepinephrine (NE); corticosterone (Cort); prolactin (PRL); adrenomedullary gene expression of catecholamine biosynthetic enzymes tyrosine hydroxylase (TH), dopamine beta-hydroxylase (DBH), and phenylethanolamine- N-methyl transferase (PNMT); and TH protein levels were measured. Ethanol-fed rats had two to threefold higher basal plasma Epi and NE and tended to have increased Cort compared to adlib-fed or pair-fed rats. Immo increased Epi and NE in ethanol-fed rats more than twofold above those observed in controls, and also increased Cort more in ethanol-fed than in control rats. PRL was marginally affected. Ethanol potentiated the normal immobilization-induced increase in adrenomedullary TH, DBH, and PNMT messenger RNA (mRNA). TH protein increased only in ethanol-fed rats. Increased plasma catecholamine levels, adrenomedullary gene expression, and TH protein concentration in nonimmobilized ethanol-fed rats strongly suggest that ethanol consumption was itself a stressor, which potentiated the subsequent response to acute Immo. Moreover, the observed interaction of ethanol and stress on plasma catecholamine levels illustrates the importance of minimizing additional stressful stimuli when investigating ethanol's physiological effects.